Religious Moderation and Cyber Social Morality: An Internalization Study among Student - Roikhatul Jannah; Saeful Bahri; Ahmad Hufron (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The rapid expansion of digital interaction among university students has created new challenges for sustaining religious moderation values in online environments. This study examines the process of internalizing religious moderation values among students of the Institut Agama Islam Bakti Negara (IAIBN) Tegal and its implications for the manifestation of their social morality in cyberspace. Amid the government’s extensive efforts to strengthen religious moderation—particularly within Islamic Higher Education Institutions (PTKI)—the digital sphere has become a dominant arena of social interaction that presents unique psychological challenges. Employing a qualitative case-study approach, this research collected data through in-depth interviews, digital participatory observation (digital ethnography), and document analysis. The data were analyzed thematically by integrating the theoretical frameworks of value internalization and John Suler’s Online Disinhibition Effect. The findings reveal that the internalization of religious moderation values at IAIBN Tegal—implemented through initiatives such as the Rumah Moderasi and curriculum integration—has been largely successful at the cognitive level. However, the manifestation of these values in students’ social morality within cyberspace remains complex and ambivalent. Online disinhibition factors—such as dissociative anonymity, invisibility, and dissociative imagination—significantly shape students’ behavior, often creating discrepancies between the values they espouse and the actions they display online. These dynamics may lead to benign disinhibition (positive openness) that aligns with moderation values, or to toxic disinhibition (aggressiveness and intolerance) that contradicts them. This study concludes that value internalization is contextual rather than absolute; the situational forces of cyberspace can temporarily override internalized values. The findings underscore the urgency for developing a “Digital Moderation Literacy” curriculum within PTKI—one that goes beyond theological knowledge transfer and equips students with metacognitive skills to consciously recognize and manage the effects of online disinhibition.